Outer membrane vesicles derived from probiotic Escherichia coli Nissle 1917 promote metabolic remodeling and M1 polarization of RAW264.7 macrophages - Ma, DongXue; Zhang, YuXin; Zhang, Jia; Shi, Jun; Gao, ShanHu; Long, Fei; Wang, Xin; Pu, XingYu; Sun, Jiayao; Liang, Shuang; Cannon, Richard D.; Villas-Boas, Silas; et al. (Frontiers in Immunology, 2025)
IntroductionEscherichia coli Nissle 1917 (EcN) is one of the most extensively studied nonpathogenic Gram-negative probiotic strains worldwide. Recent research has highlighted the ability of EcN outer membrane vesicles (OMVs) to enhance the phagocytosis and proliferation of RAW264.7 macrophages. However, the impact of EcN-OMVs on M1/M2 polarization and metabolic modulation remains unknown.MethodsIn this study, we evaluated the metabolic effects of EcN-OMVs on RAW264.7 macrophage polarization using metabolomic, transcriptomic, and fluxomic approaches.ReusltsWe found that the RAW264.7 macrophages phagocytosed EcN-OMVs, triggering upregulation of the HIF-1, mTORC1, and NF-κB signaling pathways. This metabolic reprogramming enhanced glycolysis, suppressed the TCA cycle, elevated intracellular reactive oxygen species (ROS), TNF-α, IL-6, IL-1β, ATP, and nitric oxide (NO) production, and promoted macrophage proliferation, migration, invasion, and M1-type polarization.DiscussionIn summary, this research establishes a theoretical foundation for utilizing probiotic OMVs in immunomodulatory therapeutic applications.